Anti-PD-L1 Therapy as a Solution for Non-Melanoma Skin Cancer Basal Cell Carcinoma - Rahul Simon Situmeang; Gim Mi Kyong; Rosiva Betaria Purba; Wahyu Irawati (BIOEDUSCIENCE, 2022)
Skin cancer is a disease that can cause the loss of the ability to regenerate and protect the skin normally. The types of skin cancer that are known are melanoma and non-melanoma skin cancer. Non-melanoma Basal cell carcinoma is a malignant neoplasm originating from non-keratinizing cells in the basal layer of the skin's epidermis. The treatment itself is carried out through the application of immunotherapy, namely the use of drug therapy Programmed Death Ligand 1 (PD-L1). This study aims to see the effectiveness of PD-L1 Therapy as a treatment for basal cell carcinoma. The focus of the study of the article is the integument system, skin cancer, non-melanoma basal cell carcinoma, and the effect of anti-PD-L1 use. The research method used is a literature review from various sources. Skin cancer Basal cell carcinoma attacks the basal cells of the epidermis, causing disruption. Attacks slowly, but when ignored will spread wider and more severe. Through PD-L1 therapy by binding to PD-1 receptors on immune cells, it causes the activation of T lymphocytes as anti-cancer cells in the body that suppress growth while actively controlling tumor cells. Through the use of PD-L1 therapy in treating cancer that attacks basal cells, it will suppress growth, destroy and shrink cancer cells, and increase the body's immunity against cancer cells.